Glaucoma early finding and prognosis (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Glaucoma is a unity of complex eye disorders with abnormal intraocular pressure that is enough to cause increasing cupping-ratio and visual field defect. Blindness due glaucoma is irreversible. The progress of early glaucoma can be prevented by controlling intraocular pressure at normal range using either medicament or alternative treatment i.e. massage onto the eyeball to increase the outflow facility through the trabeculum meshwork. Therefore, early diagnosis is very important and professional examination is essential. A case of an early glaucoma is reported. Treatment with asetazolamide and thymolol maleate eye drop, continued with massage onto the eyeball, had been successfull to decrease and control the intraocular pressure at normal range. Pain was disappearing and visual field defect returned to normal. Futher follow up is needed.Key words: Glaucoma - early diagnosis - controlling intra occular pressure - massage onto eyeball